2014
DOI: 10.12988/ams.2014.43168
|View full text |Cite
|
Sign up to set email alerts
|

On the first eigensurface for the third order spectrum of p-biharmonic operator with weight

Abstract: In this work, we will study the simplicity and the isolation of the first eigensurface for the spectrum of the operator Δ 2 p u+2β.∇(|Δu| p−2 Δu)+ |β| 2 |Δu| p−2 Δu, where β ∈ IR N under Navier boundary conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…and Γ p n ðβ, aÞ ⟶ ∞as n ⟶ ∞: The authors in [12] gave the first eigensurface Γ p 1 ð:,aÞ and showed that if a ≥ 0 a.e. in Ω, then Γ p 1 ð:,aÞ is simple (i. e., the associated eigenfunctions are a constant multiple of one another) and principal, i.e., the associated eigenfunction, denoted by φ p,a is positive or negative on Ω with…”
Section: Introduction and Preliminary Resultsmentioning
confidence: 99%
“…and Γ p n ðβ, aÞ ⟶ ∞as n ⟶ ∞: The authors in [12] gave the first eigensurface Γ p 1 ð:,aÞ and showed that if a ≥ 0 a.e. in Ω, then Γ p 1 ð:,aÞ is simple (i. e., the associated eigenfunctions are a constant multiple of one another) and principal, i.e., the associated eigenfunction, denoted by φ p,a is positive or negative on Ω with…”
Section: Introduction and Preliminary Resultsmentioning
confidence: 99%
“…We may now assume the following conditions: Proof. An easy adaptation of the proof of Lemma 3.4 in [12]. □ Proposition 3.10.…”
Section: Principal Eigensurfacesmentioning
confidence: 99%
“…Recently in the particular case of (1.1) where V ≡ 0 and m ≥ 0, the authors in [11], have showed that the spectrum of problem (1.1) contains at least one sequence of positive eigensurfaces. The authors in [12] have showed that the first eigensurface, in the same case, is simple and associated to positive eigenfunction. Also they showed that if m ∈ C( Ω) the first eigensurface is isolated and associated to every positive or negative eigenfunction.…”
Section: Introductionmentioning
confidence: 95%